ANALISIS PENGARUH RASIO KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS DI BURSA EFEK INDONESIA - Aini Nurkamilah, (2022)
This research is a quantitative research that aims to determine the effect of liquidity, solvency, and profitability on stock prices. The objects of this research is a Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange with an observation period of 2017 - 2021. The sample selection was carried out using a purposive sampling method and a sample of 34 Consumer Non-cyclicals companies was obtained. Liquidity variable is measured by the Current Ratio, solvency is measured by the Debt to Equity Ratio, and profitability is measured by Return On Equity. The analysis technique in this research uses panel data regression analysis with the Eviews 12 program and a significance level of 5%. The results of the test show that (1) liquidity has an effect on stock prices, (2) solvency has a negative effect on stock prices, and (3) profitability has an effect on stock prices.